Earliest Oligocene hystricognathous rodents from the Atlantic margin of northwestern Saharan Africa (Dakhla, Morocco): systematic, paleobiogeographical, and paleoenvironmental implications - (:unkn) unknown (My University, 2017)
Hystricognathous rodents are among the most common members of African mammal faunas of the mid-Paleogene, but their record has so far remained limited to North and northeast Africa. Here we report the first Paleogenerecord of hystricognaths from the Atlantic margin of North Africa. The fossils come from the westernmost part of the Sahara,east of the Dakhla peninsula, Morocco, from estuarine deposits dating to the earliest Oligocene (Dakhla level C2 [DAK C2]).Several tens of isolated teeth plus three jaw fragments document seven species of hystricognaths (Gaudeamus cf. aslius, G. cf.hylaeus, Phenacophiomys occidentalis, gen. et sp. nov., Birkamys aff. korai, Mubhammys atlanticus, sp. nov., Neophiomysminutus, sp. nov., and ?Phiocricetomys sp.). Despite the extensive east-west geographic distance, the majority ofhystricognath taxa recorded in DAK C2 document primarily close relatives of taxa that are known from a latest EoceneEgyptian locality (L-41) and from early Oligocene localities of both Egypt and Libya. This highlights the widespread eastwestdistribution of hystricognaths across North Africa, a distribution that reflects the existence of roughly similar tropicalenvironmental conditions in northern latitudes of Africa at that time. The presence of seven hystricognath species plus fiveanomaluroid species in sympatry during the earliest Oligocene demonstrates that rodents were particularly diverse near theglobal cooling recorded at the Eocene-Oligocene transition. We describe and compare the species and new species ofhystricognaths with their sub-coeval counterparts from northern and northeastern Africa and then discuss thepaleobiogeographic and paleoenvironmental implications of that discovery.
Keywords: African Research